Pengaruh Gaya Kepemimpinan Dan Kompensasi TerhadapKinerja Karyawan(Studi Pada Karyawan PT. Iskandar Indah Printing Textile Surakarta) - Bayu Aji, Yudhi; , Drs. Farid Wajdi, MM, Ph.D (2017)
The aim of this study was to analyze the influence of Leadership Style and compensation to employee performance PT. Iskandar Indah Printing Textile Surakarta partially or jointly. This type of research is quantitative, with a population of employees of PT. Iskandar Indah Printing Textile Surakarta as many as 100 employees, with a sample of 60 people. Sampling using sampling saturationor totalsampling. Methods of data collection research using a questionnaire withscale. Likert Data were analyzed using test instruments data, classic assumption test, multiple linear regression analysis. Based on the calculation of the t test, F test showed leadership style variable and compensation together have a significant influence on employee performance. Coefficient Determination R2 obtained a yield of 0.604 means that variable compensation Leadership Style and able to explain the variation of the variable changes in the performance of employees amounted to 60.4%, the rest can be explained other variables that are not included in the research model.